Efek Perlakuan Kimiawi dan Hidrotermolisis pada Biomas Tanaman Jagung (Zea mays L.) Sebagai Substrat Produksi Bioetanol - Wagiman Wagiman; Anas Miftah Fauzi; Jumali Mangunwidjaja; Sukardi Sukardi (agriTECH, 2011)
The purpose of this research was to obtain a fermentation substrate with a high content of cellulose and hemicellulose, as well as to decrease the cellulose cystalinity. Dried corn stover was crushed to pass 40 mesh, added by Ca(OH) and water, then heated at a certain time. The experimental design was prepared using a four-factor central composite design (CCD). The results of the chemical pretreatment were treated using hydrothermolysis methods for enhancing the lignin removal and decreasing cellulose crystalinity. The suitable process condition for chemical pretreatment was achieved at the loading of 0.075 g Ca(OH) /g corn stover and 6.25 ml water/g corn stover, temperature 74.6 OC at 2 hours. After hydrothermolysis, cellulose and hemicellulose were dissolved at the percentages of 52.40 % and 31.84 % respectively, while the fraction of solid substrate had a composition of cellulose of 42.68 % and hemicellulosa of 34.68 %. The crystalinity of cellulose from the leaves, cobs, and cornhusk decreased significantly. The SEM results indicated that the surface of cell wall of corn stover had been perforated by these pretreatment processes. These pores might increase the enzymatic hydrolysis of the lignocellulosic corn stover.ABSTRAKTujuan penelitian adalah mendapatkan substrat fermentasi dengan kandungan selulosa dan hemiselulosa tinggi serta menurunkan kristalinitas komponen selulosa. Limbah tanaman jagung yang sudah kering dihancurkan hingga lolos 40 mesh, ditambah Ca(OH) dan air, kemudian dipanaskan pada suhu dan waktu tertentu. Rancangan percobaan disusun dengan menggunakan central composite design (CCD) dengan empat faktor. Hasil terbaik tahap ini diberi perlakuan hidrotermolisis untuk meningkatkan penyisihan komponen lignin dan menurunkan kristalinitas selulosa. Hasil pene litian menunjukkan bahwa kondisi proses terbaik adalah penambahan 0,075 g Ca(OH) /g biomas dan 6,25 ml air/g biomas, suhu pemanasan 74,6 OC dengan waktu 2 jam. Setelah hidrotermolisis, 52,40 % selulosa dan 31,84 % hemiselulosa terlarut ke dalam air, sedangkan substrat fraksi padat memiliki komposisi selulosa 42,68 %, hemisellulosa 34,68%. Penurunan kristalinitas selulosa terjadi pada substrat dari daun, tongkol, dan kelobot. Hasil SEM mengindikasikanterbentuknya poripori pada substrat padat yang diharapkan dapat meningkatkan efektivitas hidrolisis enzimatik.